Variasi Jarak Antar Layer Bentonit Pada Pembuatan Nanokomposit Pla-Bentonit Sebagai Kemasan Makanan - Wonoputri, Vita; Emanuella, Natasha; Angelica, Evelyn; Sitompul, Johnner (Indonesian Journal of Chemical Research, 2020)
In this study, bentonite was used as a filler in the synthesis of polylactic acid (PLA) nanocomposite. The mechanical property of PLA-Bentonite nanocomposite was treated using two different surfactants, namely octadecyl amine (ODA) and trimethyl stearyl ammonium chloride (TSC) at two different concentration (20 mmol and 40 mmol). The treatments of ODA and TSC in the matrix with regards to the basal spacing of bentonite stacks measured by X-Ray Diffraction (XRD) analysis. The results showed a significant increase in basal spacing was obtained when TSC 40 was applied for treatment. Data of Fourier Transform Infrared Spectroscopy (FTIR) suggested that this increase was caused by the incorporation of surfactant into the bentonite stacks. Most of the PLA-Bentonite nanocomposite can form intercalation structure, while a sample containing TSC 40 formed exfoliation structure. This exfoliation structure resulted in a film with the best tensile strength and water vapor permeability compared to the others. The film containing TSC 40 showed the lowest reduction in water activity, almost similar to the bread sample wrapped using conventional plastic. The bread wrapped with TSC 40 film was not grown by fungi as opposed to the conventional plastic, showing the potential of the nanocomposite film as food packaging.